Fostering Interest and Critical Thinking in Mathematics Education: The Role of Integrated Evaluation Based on Linktree Platform - Ria Riyati; Winarso, Widodo (International Journal of Education and Humanities, 2024)
Based on a survey conducted by the United Nations Educational, Scientific, and Cultural Organization (UNESCO), the interest in learning among students in Indonesia is still relatively low, ranking 64th out of 120 countries. In 2007, the Global Institute reported that only 5% of students could solve high-level problem-solving tasks. This study aims to assess student responses, learning interests, and mathematical problem-solving skills following the implementation of Linktree. Linktree is an e-learning platform that offers ease in managing information despite being HTML-based. Moreover, it integrates seamlessly with various media, offers multiple tools, and presents customizable interfaces. The research methodology was quantitative, with a sample of 30 eighth-grade students from Junior high school. Data were collected through five mathematical problem-solving essay questions and questionnaires assessing student responses and learning interests post-Linktree usage. Findings revealed positive student responses towards Linktree, particularly in number patterns, with an average percentage of 84%, indicating excellent feedback. Post-Linktree usage, students exhibited an average percentage of 78% across four indicators of learning interest, classified as good. The students improved their mathematical problem-solving skills, with an average N-gain score of 0.64 and an N-gain percentage of 64.37%, categorized as moderately effective. Linktree's contribution to students' learning interest and mathematical problem-solving skills was significant, as evidenced by the hypothesis testing results, with a determination of 0.776 or 77.6% for learning interest and 0.629 or 62.9% for problem-solving skills. In conclusion, Linktree significantly contributes to students' learning interests and mathematical problem-solving skills